STRATEGIES FOR ENHANCING THE COMPETITIVENESS OF VOCATIONAL EDUCATION INSTITUTIONS: INTERNATIONAL EXPERIENCE AND LOCAL PRACTICE - Haytmetova Nasiba Narimanovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract In  the  modern  global  economy,  vocational  education  and  training  (VET) institutions play a crucial role in developing a skilled workforce capable of meeting the demands  of  rapidly  changing  labor  markets.  The  competitiveness  of  vocational education institutions has become a significant factor in ensuring educational quality, graduate  employability,  and  sustainable  socio-economic  development.  This  article examines  strategic  approaches  to  enhancing  the  competitiveness  of  vocational education  institutions  through  the  analysis  of  international  experience  and  local practice. The study explores successful models of vocational education implemented in developed countries such as Germany, Switzerland, Singapore, South Korea, and Finland,  where  strong  cooperation  between  educational  institutions  and  employers contributes to the effective preparation of qualified specialists.The research identifies key  factors  influencing  institutional  competitiveness, including  educational  quality, curriculum modernization, innovation in teaching and learning, digital transformation, labor  market  responsiveness,  quality  assurance  systems,  and  effective  institutional management.  Particular  attention  is  paid  to  the  role  of  public-private  partnerships, work-based learning, competency-based education, and international cooperation in improving institutional performance.Furthermore, the article analyzes current reforms in the vocational education system of Uzbekistan and evaluates existing challenges related  to  infrastructure  development,  teacher  qualifications,  technological modernization,  and  graduate  employment.  Comparative  analysis  demonstrates  that adapting  international  best  practices  to  local  socio-economic  conditions  can significantly  improve  the  quality  and  competitiveness  of  vocational  education institutions.  The  findings  indicate  that  sustainable  competitiveness  requires  a comprehensive  strategy  encompassing  innovation,  stakeholder  engagement, digitalization,  and  continuous  quality  improvement.The  article  concludes  that vocational  education  institutions  can  strengthen  their  competitive  position  by establishing  strong  industry  partnerships,  implementing  modern  educational technologies,  improving  governance  mechanisms,  and  ensuring  alignment  between educational outcomes and labor market requirements.